Sustainable return to work after depression - A comparative study among occupational physicians and affected employees - Ersel, Richard Paulinus; Pauli, Roman; Gaum, Petra Maria; Lang, Jessica (Frontiers in Public Health, 2022)
Introduction. The number of sick days taken from work due to depression is steadily rising. A successful return to work (RTW) is essential for sustainable reintegration. This study aims to identify factors to optimize RTW and to investigate approaches for sustainable RTW (sRTW) after depressive episodes. Methods. Semi-structured expert interviews with senior occupational physicians (OPs, N=5) served to develop two surveys among OPs (N=180) and employees after depressive episode (N=192). Predictors of RTW rating, workplace-based RTW interventions and sRTW interventions were analyzed using multiple hierarchical regression, chi-square difference and t-tests. Results. For OPs, employee training on mental illness prevention was found to be the strongest predictor of overall RTW rating, whereas understanding and appreciation in conversations and stigmatization were strongest predictors of overall RTW rating by the employees. Compared to the employees, OPs reported significantly more availability of workplace-based interventions. To prevent relapse, the employees prioritized sufficient time and financial security during the RTW process more than OPs. Conclusions. The study identified facilitating and hindering factors that can inform further research and practice to improve RTW after depressive episodes. To redress the awareness gap about the availability of workplace-based interventions, regular contact between OPs and employees is crucial. Several factors were considered to be of varying importance for relapse prevention by the two groups. Multiple perceptions and needs ought to be taken into account during RTW.